La poesía de Fawziyya Abū Jālid y su repercusión en la sociedad saudí actual - Prieto Velasco, Paola (Anaquel de Estudios Árabes, 2020)
Fawziyya Abū Khālid is a poet from Saudi Arabia, born in Riyadh in 1955. Her poems are appreciated for their form and especially for their content. Through free and blank verses, Abū Khālid expresses all types of human concerns that she shares with lots of her compatriots, such as a woman’s freedom, her relation with men and her identity. It is possible that, in a Western context, these subjects are admirable but not out of the ordinary. Nevertheless, we have to situate ourselves in a Saudi Arabia in which, still in the 21st century, women are subjugated by men in most situations. These issues are those the poet addresses, using language with which she approaches all audiencies and a courage that has earned her the right to become the voice of many Saudi women. Apart from having this important role, Fawziyya Abū Khālid is recognized as one of the most relevant poets of the current Arab landscape for focusing on ideas such as national identity and the support for the Palestinian cause by means of the written word.